Effect of scoria powder on the strength and porosity of porous concrete produced with recycled porous concrete aggregate - Demet Yavuz (Engineering Science and Technology, an International Journal)
In recent years, there has been a significant increase in the cycle of demolition and reconstruction, driven by the growing demand for housing and urbanization in developing countries. As new buildings are constructed at a rapid pace, the resulting debris from older structures presents a considerable challenge, particularly because of limited storage capacity. This study focused on the production of porous concretes using recycled aggregates. To address the low strength associated with recycled aggregates, 5 % (by weight) of silica fume was incorporated, while scoria was used to replace cement at varying levels of 5 %, 10 %, 15 %, 20 %, 25 %, and 30 % by weight. The research also analyzed the pore structure and distribution within the porous concrete through computed tomography, with an emphasis on its mechanical properties, porosity, and water permeability. The results demonstrate that scoria serves effectively as a binder, successfully substituting for cement. Additionally, the integration of scoria enhanced the compressive strength of the porous concrete after a 120-day curing period, due to pozzolanic reaction caused by scoria, while also reducing water permeability.